TEKA-TEKI MASYARAKAT DI NAGARI III KOTO AUR MALINTANG TIMUR KECAMATAN IV KOTO AUR MALINTANG KABUPATEN PADANG PARIAMAN - Armayunita, Weni; Hayati, Yenni; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2017)
This study aimed to describe the structure, category, and function of the public puzzle in Nagari Koto Aur Malintang III Eastern District of IV Koto Aur Malintang Padang Pariaman district. This study uses qualitative descriptive form. Sources of data in this research puzzle community in Nagari Koto Aur Malintang III Eastern District of IV Koto Aur Malintang Padang Pariaman district. Based on the research results, puzzles society in Nagari Koto Aur Malintang III East, we can conclude the following. First, the structure of the puzzle consists of elements (descriptive) and the picture element (referent)answers. Second, based on the nature of things depicted in question, the category of puzzle community in Nagari III Koto Aur Malintang East can be grouped into four, namely: (1) equality with man found 25 of the 60 puzzle, (2) equality with animals found 8 of 60 puzzles, (3) the equation with the found objects 13 of 60 puzzles, and (4) equations with plants found 14 of the 60 puzzles. Third, Puzzle has three functions, namely the function to deliver education, training functions of the intellect, and function as entertainment.Keywords: Structure, category, and function